2016
DOI: 10.1111/aor.12691
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Conditioning After Cardiac Arrest: The Use of Normothermic Extracorporeal Membrane Oxygenation in the Non‐Heart‐Beating Animal Model

Abstract: The effect of normothermic extracorporeal membrane oxygenation (NECMO) on small bowel preservation in a clinically relevant large animal model of expected donation after cardiac death (eDCD) was evaluated. Thirty domestic crossbred donor pigs were divided into five groups. The first group served as the live donation (LD) group, the second group served as the donation after cardiac death (DCD) group, and the remaining were further assigned into three subgroups: E1 group (1 h NECMO support), E3 group (3 h NECMO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In previous studies, ECMO technology was used in the field of DCD donor bowel preservation 4 . The analyses demonstrated that normothermic extracorporeal support for 1 hour in DCD was beneficial for improving the energy status and viability of the bowel.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous studies, ECMO technology was used in the field of DCD donor bowel preservation 4 . The analyses demonstrated that normothermic extracorporeal support for 1 hour in DCD was beneficial for improving the energy status and viability of the bowel.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal mucosal biopsy samples of the grafts were obtained for histologic examination, transmission electron microscopy, Western blotting of tight junction proteins, and cell apoptosis examination as described previously 4 . Histologic injury of the intestinal samples was quantitatively evaluated using the scoring system of Chiu et al in a blinded manner 6 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations